Phytodrugs with anabolic effect - Zaychenko, G. V.; Gorchakova, N. O.; Belenichev, I. F.; Shumeiko, O. V.; Klymenko, O. V.; Doroshenko, A. I.; Kovtun, D. O.; Зайченко, Г. В.; Горчакова, Н. О.; Бєленічев, Ігор Федорович; Шумейко, О. В.; Клименко, О. В.; et al. (My University, 2023)
Galenic and neogalenic phytodrugs, which were widely used in traditional medicine, have not lost their importance even today due to their lower cost, lower toxicity and wide spectrum of action and availability. Special attention began to be paid to medicinal phytozamobs, which can activate protein and nucleic acids associated with work capacity and are used not only for physical exertion, but also for military and clinical purposes, for diseases of internal organs, cardiovascular and nervous systems , during the period of viral and infectious diseases. One of the first plants whose root extract was found to have an anabolic effect was creeping wheatgrass. Already in experiments on intact anesthetized rats, the level of total protein, which is associated with the activation of the level of nucleic acids, increased in the tissues of the liver, kidneys and heart when intramuscularly the extract of creeping tyria was administered. Pharmacological anabolic activity of creeping wheat extract was also confirmed in experiments on rats with food deprivation and hydro-induced cortisol-induced protein catabolism. Food deprivation was simulated by leaving animals without food for 7 days. Hydrocortisol suspension was administered intramuscularly to rats for 8 days. The anabolic effect of the creeping wheat extract exceeded the effect of the reference drug potassium orotate. It has been established that, in addition to the anabolic effect, the extract of creeping wheat also has an immunomodulatory, antioxidant, and anti-inflammatory effect, which is the basis for the possibility of its use in clinical practice. Metabolic and anabolic activity was also established in the wild wolf. At the same time, attention was paid to wound-healing, immunomodulating effects. At the same time, anti-inflammatory, adhesive, hepatoprotective, diuretic, antioxidant, vasodilator, hypoazotemic activity was established. Preparations of beet roots, along with anabolic activity, also show hypoglycemic, antichenobacterial effect, and also normalized blood pressure, revealed antioxidant, anti-ischemic, cardioprotective, neuroprotective and antioxidant activity, influencing the content of nitric oxide. Due to the presence of phytosterols, organic acids and other biologically active substances, the extract of the roots of creeping wheatgrass, field wolfberry, prickly wheatgrass and beetroot has an anabolic, organoprotective, reparative, hepatoprotective, diuretic, antioxidant, vasodilator, anti-inflammatory, hyponitrogenous effect. Галенові і новогаленові фітопрепарати, що широко застосовували в народній медицині, не втратили свого значення і сьогодні завдяки меншій вартості, меншій токсичності і широкому спектру дії та доступності. Метою дослідження є визначення анаболічних та інших метаболічних властивостей у фітопрепаратів пирію повзучого, буряка та вовчуга. Об’єкт і методи дослідження. За темою дослідження проведений пошук і аналіз наукової літератури, включаючи PubMed, Google Scholar, Scopus. Результати. Однією з перших рослин, у екстракті коренів якої визначили анаболічний вплив був пирій повзучий. Фармакологічна анаболічна активність екстракту пирію повзучого була підтверджена також в експериментах на щурах з харчовою депривацією та гідроіндукованим кортизоліндукованим катаболізмом білків. Анаболічна дія екстракту пирію повзучого перевищувала ефект референтного препарату калію оротату. Встановлено, що крім анаболічної дії екстракт пирію повзучого володіє також імуномодулюючим, антиоксидантним, протизапальним ефектом, що є підставою для можливості призначення в клінічній практиці. Метаболічну та анаболічну активність встановили також у вовчуга польового. При цьому звернули увагу на ранозагоюючу, імуномодулюючу дії. Одночасно встановили протизапальну, адгезивну, гепатопротекторну, діуретичну, антиоксидантну, судинорозширювальну, гіпеазотемічну активність. Препарати коренів буряка, поряд з анаболічною активністю, проявляють також цукрознижуючу, антихенобактерну дію, а також нормалізували артеріальний тиск, виявили антиоксидантну, протиішемічну, кардіопротекторну дію, нейропротекторну та антиоксидантну активність, впливаючи на вміст оксиду азоту. Екстракт коренів пирію повзучого, вовчуга польового, пирію колючого і буряка, завдяки наявності фітостеролів, органічних кислот та інших біологічно активних речовин, проявляють анаболічну, органопротекторну, репаративну, гепатопротекторну, діуретичну, антиоксидантну, судинорозширювальну, протизапальну, гіпоазотенічну дію. Висновки. Представлені літературні дані свідчать, що екстракти пирію, вовчуга і соку буряка володіють анаболічною та широким спектром метаболічної дії, що є підставою для включення їх як харчової домішки при лікуванні захворювань серцево-судинної, нервової системи, гормональних розладів, порушень травного каналу.
Фітопрепарати з анаболічною дією
Belenichev I. F. - https://orcid.org/0000-0003-1273-5314
Keywords: extract of the roots of creeping wheat; extract of beet roots; extract of wild lupine; anabolic action; екстракт коренів пирію повзучого; екстракт коренів буряка; екстракт вовчуга польового; анаболічна дія